Hydraulic Fractures Productivity Performance in Tight Gas Sands — A Numerical Simulation Approach - Ostojic, J.; Rezaee, M. Reza; Bahrami, Hassan (Australian Petroleum Production and Exploration Association, 2011)
The increasing global demand for energy along with the reduction in conventional gas reserves has lead to the increasing demand and exploration of unconventional gas sources. Hydraulically-fractured tight gas reservoirs are one of the most common unconventional sources being produced today and look to be a regular source of gas in the furture. Hydraulic fracture orientation and spacing are important factors in effective field drainage and gas recovery. This paper presents a 3D single well hydraulically fractured tight gas model created using commercial simulation software, which will be used to simulate gas production and synthetically generate welltest data. The hydraulic fractures will be simulated with varying sizes and different numbers of fractures intersecting the wellbore. The focus of the simulation runs will be on the effect of hydraulic fracture size and spacing on well productivitiy performance. The results obtained from the welltest simulations will be plotted and used to understand the impact on reservoir response under the different hydraulic fractured scenarios. The outputs of the models can also be used to relate welltest response to the efficiency of hydraulic fractures and, therefore, productivity performance.